To solve the quadratic equation \( x^2 + 2x - 8 = 0 \) by completing the square, follow these steps:
-
Start with the equation: \[ x^2 + 2x - 8 = 0 \]
-
Move the constant term to the other side: \[ x^2 + 2x = 8 \]
-
Complete the square on the left side. To do this, take half of the coefficient of \( x \) (which is \( 2 \)), square it, and add it to both sides:
- Half of \( 2 \) is \( 1 \), and squaring it gives \( 1 \).
- Add \( 1 \) to both sides: \[ x^2 + 2x + 1 = 8 + 1 \] \[ x^2 + 2x + 1 = 9 \]
-
Now, the left side can be factored: \[ (x + 1)^2 = 9 \]
-
Take the square root of both sides: \[ x + 1 = 3 \quad \text{or} \quad x + 1 = -3 \]
-
Solve for \( x \):
- From \( x + 1 = 3 \): \[ x = 3 - 1 = 2 \]
- From \( x + 1 = -3 \): \[ x = -3 - 1 = -4 \]
Thus, the solutions to the equation \( x^2 + 2x - 8 = 0 \) are \( x = 2 \) and \( x = -4 \).
Therefore, the correct response is:
x=2, x=−4
x equals 2 , x equals negative 4